Relationship between UDP-Glucose 4-Epimerase Activity and Oligoglucose Glycoforms in Two Strains of Neisseria meningitidis - Lee, Frank K. N. (American Society for Microbiology, 1999)
Sodium dodecyl sulfate-polyacrylamide gel analysis of lipooligosaccharide (LOS) from Neisseria meningitidis has demonstrated considerable microheterogeneity in the variable region of LOS due to the presence of novel glycoforms. As a step toward understanding the basis for the expression of these novel glycoforms, we have examined the LOS structures and UDP-glucose 4-epimerase (epimerase) activity levels in two strains (NMB and MA-1) and their respective galE mutants. Strain NMB was found to have low epimerase activity and to contain multiple glycoforms, some of which appear to contain only glucose sugars. The galE mutant had only the oligoglucose glycoforms. Strain MA-1 had higher epimerase activity at both log and stationary phases (2- and 12.5-fold, respectively) and one glycoform with a putative lactosyl structure. Strain MA-1 galE had two glycoforms that contained one or two glucose residues. To understand the molecular basis for the different epimerase activities, we examined the predicted amino acid sequences of the respective galE open reading frames and determined the relative amounts of GalE protein. We found no significant differences between the predicted amino acid sequence of the GalE protein in NMB and that in MA-1. We observed no significant differences in the level of GalE protein between MA-1 and NMB at exponential or stationary phase. We also observed an 8.2-fold drop in epimerase activity in NMB between the log and stationary phases that was not due to the GalE protein level or low glucose levels.